2004
DOI: 10.4049/jimmunol.173.4.2683
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Binding Protein Binds to Triacylated and Diacylated Lipopeptides and Mediates Innate Immune Responses

Abstract: LPS binding protein (LBP) is an acute-phase protein synthesized predominantly in the liver of the mammalian host. It was first described to bind LPS of Gram-negative bacteria and transfer it via a CD14-enhanced mechanism to a receptor complex including TLR-4 and MD-2, initiating a signal transduction cascade leading to the release of proinflammatory cytokines. In recent studies, we found that LBP also mediates cytokine induction caused by compounds derived from Gram-positive bacteria, including lipoteichoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
5
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 64 publications
(74 reference statements)
4
119
5
4
Order By: Relevance
“…Notably, it has been established that OxPAPC binds to serum accessory proteins such as LBP and CD14 and competitively inhibits the binding of LPS to these proteins (17). Likewise, it has been shown that both di-acyl and tri-acyl bacterial lipopeptides bind to CD14 and LBP (35,47) and that CD14 and LBP are required for enhanced cellular sensitivity to bacterial lipopeptides (32,34). Thus, it is likely that the established binding of OxPAPC to CD14 and LBP (17) also contributes to the inhibition of cellular responsiveness to lipopeptides via TLR2.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it has been established that OxPAPC binds to serum accessory proteins such as LBP and CD14 and competitively inhibits the binding of LPS to these proteins (17). Likewise, it has been shown that both di-acyl and tri-acyl bacterial lipopeptides bind to CD14 and LBP (35,47) and that CD14 and LBP are required for enhanced cellular sensitivity to bacterial lipopeptides (32,34). Thus, it is likely that the established binding of OxPAPC to CD14 and LBP (17) also contributes to the inhibition of cellular responsiveness to lipopeptides via TLR2.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, most in vivo relevant lipopeptides are triacylated and, therefore, are adequately modeled by Pam3Cys used in our study (28,64). Respiratory viruses that can activate TLR2 (29,63) also have been associated with MS exacerbations (31,32,61).…”
Section: Foxp3mentioning
confidence: 99%
“…3A). It has been shown that PGN directly binds TLR2 per se (40), whereas bacterial lipopeptides are thought to directly interact with TLR2-associated molecules such as CD14 and LBP but not with TLR2 per se (7,41,42), suggesting the existence of different ligand-recognition mechanisms by TLR2. Furthermore, a novel family of PGN-binding proteins such as peptidoglycan recognition proteins has been found (43) and might enable discrimination of PGN from other TLR2 agonists.…”
Section: Volume 282 • Number 11 • March 16 2007mentioning
confidence: 99%